ONLINE SURFACE CONDITION MONITORING SYSTEM USING TIME FREQUENCY DISTRIBUTION ON HIGH VOLTAGE INSULATOR - Abdullah, Abdul Rahim; zainal, Nur Qamarina; NORDDIN, NURBAHIRAH; Aman , Aminudin (AENSI Publications, 2013)
Polymeric composite insulation is widely used for high voltage engineering as they are light, easy to fabricate, and have good dielectric properties. Ageing factors are several factors that affect the long term performance of insulating material. One of the key methods to measure the expected physical, chemical change, hydrophobicity condition as well as surface condition is leakage current characteristic. Leakage current is broadly accepted as tools in the determination of surface condition and level of its severity. Hence, an automated monitoring system is needed to reduce diagnostic time, rectify severity and ensure quality of insulators performance. Fast Fourier Transform gives useful information on the analysis of leakage current, but it has some limitation in non-stationary signal that does not provide temporal information. Instead, the new leakage current analytical technique with time frequency distribution approach is employed. This research used spectrogram as time frequency distribution technique that represents the leakage current signals in the joint time frequency domains which they are very appropriate to analyse the leakage current signals that consist of multi-frequency components and magnitude variations. Signal parameters such as instantaneous root mean square and fundamental root mean square current, total harmonic distortion, total non-harmonic distortion, and total waveform distortion are estimated from time-frequency representation. Tracking and erosion test complying with BS EN 60587-2007 are conducted to capture the set of leakage current patterns which are capacitive, resistive, and discharge activities. Based on the analysis, the severity of the insulators could be determined from the percentage of total waveform distortion. Thus, the outcome of this study shows that the system is very appropriate and reliable to be implemented for leakage current online monitoring system.